2019
DOI: 10.1111/bjd.17940
|View full text |Cite
|
Sign up to set email alerts
|

Thymic stromal lymphopoietin production induced by skin irritation results from concomitant activation of protease‐activated receptor 2 and interleukin 1 pathways

Abstract: Summary Background Thymic stromal lymphopoietin (TSLP) mediates proallergic T helper 2‐type responses by acting on leucocytes. Endogenous pathways regulating TSLP production are poorly defined. Objectives To uncover the mechanisms by which skin barrier disruption elicits TSLP production and to delineate the level at which individual mechanistic components may converge. Methods A combination of primary keratinocytes, skin explants and in vivo strategies was employed. Murine skin was tape stripped in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…Following up on this finding, we recently reported that TSLP efficiently maintains survival of skin MCs by acting through a complex mechanism composed of two parallel axes, i.e., STAT5/Mcl-1 and JNK/Bcl-xl [ 44 ]. While being renowned for its Th2 skewing potential, TSLP can, in addition to these more long-term effects, act as an epithelial alarmin, that is swiftly synthesized and released upon tissue damage, including microbial challenge, trauma, and physical or chemical insults [ 45 , 46 , 47 ]. Under these circumstances, TSLP can act acutely, and MCs are ideally positioned in tissues to swiftly respond to and integrate signals from infectious agents, allergens, drugs and tissue-derived alarmins.…”
Section: Introductionmentioning
confidence: 99%
“…Following up on this finding, we recently reported that TSLP efficiently maintains survival of skin MCs by acting through a complex mechanism composed of two parallel axes, i.e., STAT5/Mcl-1 and JNK/Bcl-xl [ 44 ]. While being renowned for its Th2 skewing potential, TSLP can, in addition to these more long-term effects, act as an epithelial alarmin, that is swiftly synthesized and released upon tissue damage, including microbial challenge, trauma, and physical or chemical insults [ 45 , 46 , 47 ]. Under these circumstances, TSLP can act acutely, and MCs are ideally positioned in tissues to swiftly respond to and integrate signals from infectious agents, allergens, drugs and tissue-derived alarmins.…”
Section: Introductionmentioning
confidence: 99%
“…TSLP is associated with inflammatory processes of the skin and disorders like atopic dermatitis . To induce TSLP production, keratinocytes were stimulated with IL‐1β and TLR3‐l based on previous studies from our laboratory .…”
Section: Resultsmentioning
confidence: 99%
“…Thymic stromal lymphopoietin (TSLP), an influential keratinocyte‐derived mediator, is triggered by physical, chemical, or biological disturbance of skin homeostasis . It is directly associated with inflammatory and hypersensitivity responses occurring at barrier surfaces, as well as with Th2 immunity and chronic dermatoses like atopic dermatitis (AD) and psoriasis .…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the study by Redhu et al . shows how skin irritation can aggravate atopic eczema or trigger flares: IL‐1 and PAR‐2 pathways are activated and then cooperate in driving TSLP production, which secondarily promotes Th2 differentiation, Th2 cell proliferation as well as the production of Th2 cytokines .…”
mentioning
confidence: 99%